Gambaran Kejadian Shivering Pasien dengan Metode Spinal Anestesi Enhanced Recovery After Surgery (ERAS) - Galih Pria Pambayun; Nabhani Nabhani; Afina Rizkaningsih (Quantum Wellness : Jurnal Ilmu Kesehatan, 2024)
Background : Spinal anesthesia techniques are mostly used in obstetric surgery, especially sectio caesarea, which can be seen from the birth rate through sectio caesaria, which is 9.8% of 49,603 births in Indonesia, data collected from 2010-2013. The most common complication is post-anesthesia shivering. Shivering after anesthesia can occur in 33-56.7% of patients using spinal anesthesia. Objective : This research aims to describe post-anesthetic shivering the use of the spinal anesthesia enhanced recovery after surgery (ERAS) method with the NON-ERAS.. Research Methods : This research uses Quasi Experiment Observational design. Sampling technique with purposive sampling. Samples were 60 samples of sectio caesarea patients. Test data analysis with Mann Whitney. Shivering incident data was taken from the shivering score observation sheet with a value of 0 to 4. Results : The analysis indicated that the most frequently observed degree of shivering was grade 0, accounting for 16 samples (53.3%) in the ERAS spinal anesthesia group and 15 samples (50%) in the Non-ERAS group. The absence of shivering was more prevalent in both groups, observed in 26 samples (86.7%) in the ERAS spinal anesthesia group and 19 samples (63.3%) in the Non-ERAS group. Conclusion : Conclusions of the research, there is a difference in the incidence of shivering in the ERAS spinal anesthesia method and the non-ERAS spinal anesthesia method.